Pharmacological and Therapeutic Effects of Triphala –Churna (Asian Journal of Pharmaceutics (AJP), 2025)
Triphala is a customary Ayurvedic course of action made from three Indian domestic developed common items:Terminalia chebula, Phyllanthus emblica, and Terminalia belerica. It is a tridoshic rasayana that equalizationsand rejuvenates the three sacrosanct components that regulate human life. Triphala is affluent in canceranticipation operators, antibacterial, anti-viral, and anti-cancer properties, and is known to cure cataract and treatSecured Secure Need Clutter (Makes a difference). It is a polyherbal definition with a one of a kind componentof movement, profitable for all three doshas (vata, pitta, and kapha) and contains compounds such as gallicdestructive, chebulagic destructive, and chebulinic destructive. Triphala’s tall Vitamin C substance and linoleicoil make it a tonic. It has different antioxidant, anti-inflammatory, antipyretic, torment diminishing, antibacterial,antimutagenic, wound recovering, anti-cariogenic, antistress, adaptogenic, anti-diabetic, and hypoglycaemicproperties.